Does postimplantation syndrome due to endovascular aneurysm repair increase mortality rate? (Annals of Medical Research, 2021)
Aim: Postimplantation syndrome diagnosed by high levels of white blood cell and c-reactive protein or fever is an inflammatory clinical finding after endovascular aneurysm repair. We aimed to analyze whether it can increase mortality rate or not.Material and Methods: A literature search was performed in electronic database, Pubmed, without date limitation. Trials that compare the rate of mortality between patients with postimplantation syndrome and controls were included. Date of articles and numbers of death in each groups were noted. The results of studies were evaluated by random or fixed effect model according to heterogeneity. Statistical analysis was performed by using Jamovi software.Results: After the database search, we attained in all 358 articles. After overview of titles and abstracts, we included 5 articles in the meta-analysis which contained 1283 patients and abided by inclusion criteria. In analysis, it was observed that there was no significant difference for mortality between patients with postimplantation syndrome and controls (OR: 0.27, 95% CI -0.27-0.81 and p=0.33. Studies included in the analysis were not heterogeneous (I2=6.63%). Possible publication bias was found (tau2:0.0). The weight of one of five studies with regard to results of analysis was 57.7%.Conclusion: We concluded that postimplantation syndrome cannot increase mortality, though it’s high development rate after endovascular aneurysm repair.
Keywords: Endovascular aneurysm repair; mortality; postimplantation syndrome